Effects of wind-wave disturbance and nutrient addition on aquatic bacterial diversity, community composition, and co-occurrence patterns: A mesocosm study - Shen, Zhen; Xie, Guijuan; Tian, Wei; Shao, Keqiang; Yang, Guijun; Tang, Xiangming (Current research in microbial sciences, 2022)
•Bacterial diversity in disturbed conditions increased significantly.•Bacterial diversity in nutrient addition decreased significantly.•Bacterial community composition in disturbances and nutrient addition exhibited different variations.•Nutrient input enhance positive interactions among bacteria.•Disturbance indirectly influenced bacterial community composition by affecting algal community composition. Wind-wave disturbance and nutrient input are the major environmental factors that shape bacterial diversity and community composition in lakes. However, knowledge of bacteria as bio-indicators’ synergistic response to disturbance patterns and nutrient addition is still poor. To address this knowledge gap, we conducted a mesocosm experiment over 21 days, and collected 90 water samples from tanks under six different patterns of disturbance and nutrient addition; we explored the bacterial communities using high-throughput 16S rRNA gene sequencing. We found significantly increased bacterial diversity in continuously disturbed conditions and in intermittently disturbed conditions, and significantly decreased bacterial diversity under the synergistic effect of disturbances and nutrients. Bacterial community composition (BCC) under conditions of disturbance and nutrient addition exhibited different variations. However, there were no significant differences in BCC between continuously and intermittently disturbed mesocosms. Co-occurrence networks analysis showed that the proportion of positive correlations among edges in nutrient addition conditions were significantly higher than that in disturbed condition, indicating that nutrient input may increase the proportion of niche overlap, and enhance positive interactions among bacteria. Meanwhile, the co-occurrence patterns between algal and bacterial communities suggested shared environmental preferences or potential interactions among these two groups. Our study provides a new insight into the restoration of shallow eutrophic lake ecosystems. Moreover, the different distribution patterns of bacterial community act as ecological indicators of response to disturbances and nutrient input. [Display omitted]